Viabilidade do escaneamento intraoral no ensino superior em odontologia em uma universidade pública - Miranda, Amanda Silva (2023)
The teaching of digital flow with scanners in postgraduate and specialization courses is already well-established, but there is a gap in its use in undergraduate teaching. The aim of this study was to assess the feasibility of intraoral scanning in undergraduate dental education at a public university, from three different perspectives: the undergraduate teacher, the undergraduate student and the patient who underwent the procedure. Three different questionnaires were developed and applied to the volunteer participants: 25 patients answered 18 questions, 27 students answered 7 questions and 11 teachers answered 8 questions. For statistical analysis, Pearson's correlation test was carried out between the perceptions of the variables involving each of the procedures, and the T-test was also carried out (p <0.05). A statistical correlation was found between nausea and procedure time, and also between nausea and the taste of the impression material. The descriptive results showed that the patients varied in age (7 years to 73 years), preference for scanning, the procedure as a whole, mouthpiece size, occlusal registration, clinical time, taste and nausea. The students ranged in age from 21 to 31, 85% had to repeat the impression and 19 felt partially comfortable taking the impression. The teachers' ages ranged from 30 to 59. All the teachers had to intervene in the molding and 81% believed that the students were able to finish the procedure well. All the students and teachers considered the introduction of scanning in the undergraduate program to be important. In terms of the university's costs, scanning proved to be the least expensive due to the number of repetitions carried out in the undergraduate clinic. The innovation of the project was the possibility of comparing costs, comfort and clinical time, promoting impact in multidisciplinary environments and at the university. The conclusion is that scanning was better for the patient than impression taking, and for students and teachers, it is important to teach new technologies in undergraduate courses.